Enacting intersectional multilayered citizenship: Kurdish women's politics - Erel, Umut; Acik, Necla (Gender, place and culture : a journal of feminist geography, 2020)
Focusing on the institutional aspects of the Kurdish women's movement in Turkey since the 1990s the article shows how it established a consciousness within the Kurdish national movement that gender equality is a cornerstone of democracy and ethnic rights. We frame this through theories of enacting intersectional multilayered citizenship and identify three key interventions: autonomous women's assemblies, women's quotas in pro-Kurdish rights parties and the co-chair system where all elected positions within the pro-Kurdish parties are jointly occupied by a male and female. These have achieved a better representation of women in formal politics, rendered gender equality and sexual violence legitimate subjects of politics and contributed to establishing an aspiration for a more dialogic political ethos. While the women's movement's close affiliation with the Kurdish national movement has been highly effective, it also in part circumscribes gender roles to fit its agendas.